Nutritive value of fermented palm oil sludge added with different sources of phosphorus - Tiurma Pasaribu; N Arini; T Purwadaria; A.P Sinurat (Indonesian Center for Animal Research and Development (ICARD), 2003)
The experiment has been conducted to determine the nutritive value of palm oil sludge fermented with A. niger added with different sources of phosphorus (NPK, P2O5, NaH2PO4). The experiment was assigned in a factorial (3x3) design. The main factor was sources of phosphorus, while the sub factor was time of incubation (0, 4 days aerobic incubation, and 4 days aerobic incubation followed by 2 days anaerobic incubation). Parameters measured were pH, soluble nitrogen, true protein and crude protein, total α-amino acid (TAAA), soluble phosphorus and total phosphor, in vitro dry matter (DCBK), and true protein digestibilities (DCP). Results from the analyses showed that fermentation increased the contents of soluble and total P, protein and TAAA and the value of in vitro protein digestibility. Fermented product added with P2O5 had the highest in vitro dry matter digestibility, while the one added with NPK had true protein content and digestibility. It was concluded that additional NPK gave the best result interm of nutritive value. Key words: Palm oil sludge, A. niger, phosphorus sources